Policy Brief 1: Can a behavioural approach help fight corruption? - Baez Camargo, Claudia (Basel Institute on Governance Policy Briefs, 2017)
This Policy Brief summarises the lessons learned from a systematic literature review that explored the feasibility of adopting a behavioural approach to address petty corruption. The findings point to the importance of developing messages that challenge conventional wisdom about the inevitability of corruption, emphasising the costs of corruption to the welfare of individuals as well as showcasing examples of successful detection and punishment of crimes of corruption. Accounting for prevailing social norms and beliefs is also key because otherwise anti-corruption interventions may disseminate concepts and promote actions that fail to deliver the desired messages to their intended beneficiaries.